GlobSed: Updated Total Sediment Thickness in the World's Oceans - Straume, Eivind O; Gaina, Carmen; Medvedev, Sergei; Hochmuth, Katharina; Gohl, Karsten; Whittaker, Joanne; Abdul Fattah, R; Doornenbal, J C; Hopper, John R (Geochemistry, Geophysics, Geosystems, 2019)
We present GlobSed, a new global 5-arc-minute total sediment thickness grid for the world's oceans and marginal seas. GlobSed covers a larger area than previously published global grids and incorporates updates for the NE Atlantic, Arctic, Southern Ocean, and Mediterranean regions, which results in a 29.7% increase in estimated total oceanic sediment volume. We use this new global grid and a revised global oceanic lithospheric age grid to assess the relationship between the total sediment thickness and age of the underlying oceanic lithosphere and its latitude. An analytical approximation model is used to mathematically describe sedimentation trends in major oceanic basins and to allow paleobathymetric reconstructions at any given geological time. This study provides a much-needed update of the sediment thickness distribution of the world oceans and delivers a model for sedimentation rates on oceanic crust through time that agrees well with selected drill data used for comparison.
Keywords: Sørishavet; batymetri; litosfæren; marin geofysikk; marin geologi; sedimenter; sedimentologi

Crustal structure and tectonic provinces of the Riiser-Larsen Sea area (East Antarctica): results of geophysical studies - Leitchenkov, German; Guseva, J; Gandyukhin, V; Grikurov, G; Kristoffersen, Yngve; Sand, M; Golynsky, A; Aleshkova, N (Marine Geophysical Researches, 2008)
Keywords: Sørishavet; kontinentalmargin; marin geofysikk; seismologi; stratigrafi

The Cosmonaut Sea Wedge - Solli, Kenneth; Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J; Gandyukhin, V (Marine Geophysical Researches, 2008)
Keywords: Sørishavet; kontinentalmargin; marin geofysikk; sedimenter

Interplay of turbidite and contourite deposition along the Cosmonaut Sea/Enderby Land margin, East Antarctica - Kuvaas, Berit; Kristoffersen, Yngve; Guseva, J.; Leitchenkov, German; Gandjukhin, V.; Løvås, O.; Sand, Morten; Brekke, Harald (Marine Geology, 2005)
Multichannel seismic reflection data from the Cosmonaut Sea margin of East Antarctica have been interpreted in terms of depositional processes on the continental rise. A major sediment lens is present below the upper continental rise along the entire Cosmonaut Sea margin. The lens probably consists of sediments supplied from the shelf and slope, being constantly reworked by westward flowing bottom currents redepositing the sediments into a large-scale plastered drift deposit prior to the main glacigenic input along the margin. High-relief elongated and sometimes semicircular depositional structures are found on the upper continental rise, stratigraphically above the regional sediment lens, and were mainly deposited by the action of closely spaced turbidity currents. On the lower continental rise, large-scale sediment bodies extend perpendicular to the continental margin and were deposited as a result of down-slope turbidity transport and westward flowing bottom currents. The elongated sediment mounds on the upper and lower continental rise were deposited after initiation of glacigenic input to the slope and rise.
Keywords: Antarktis; Sørishavet; marin geofysikk; marin geologi

Input of Glaciomarine Sediments along the East Antarctic Continental Margin; Depositional Processes on the Cosmonaut Sea Continental Slope and Rise and a Regional Acoustic Stratigraphic Correlation from 40° W to 80° E - Kuvaas, Berit; Kristoffersen, Yngve; Guseva, J.; Leitchenkov, German; Gandjukhin, V; Kudryavtsev, Genadii (Marine Geophysical Researches, 2004)
Multichannel seismic reflection data from the Cosmonaut Sea margin of East Antarctica have been interpreted in terms of depositional processes in the continental slope and rise area. A major sediment lens is present below the upper continental rise along the entire Cosmonaut Sea margin. The lens probably consists of sediments supplied from the shelf and slope, being constantly reworked by westward flowing bottom currents, which redeposited the sediments into a large scale drift deposit prior to the main glaciogenic input along the margin. High-relief semicircular or elongated depositional structures are also found on the upper continental rise stratigraphically above the regional sediment lens, and were deposited by the combined influence of downslope and alongslope sediment transport. On the lower continental rise, large-scale sediment bodies extend perpendicular to the continental margin and were deposited as a result of downslope turbidity transport and westward flowing bottom currents after initiation of glacigenic input to the slope and rise. We compare the seismostratigraphic signatures along the continental margin segments of the adjacent Riiser Larsen Sea, the Weddell Sea and the Prydz Bay/Cooperation Sea, focussing on indications that may be interpreted as a preglacial-glaciomarine transition in the depositional environment. We suggest that earliest glaciogenic input to the continental slope and rise occurred in the Prydz Bay and possibly in the Weddell Sea. At a later stage, an intensification of the oceanic circulation pattern occurred, resulting in the deposition of the regional plastered drift deposit along the Cosmonaut Sea margin, as well as the initiation of large drift deposits in the Cooperation Sea. At an even later stage, possibly in the middle Miocene, glacial advances across the continental shelf were initiated along the Cosmonaut Sea and the Riiser Larsen Sea continental margins.
Keywords: Sørishavet; Weddellhavet; marin geofysikk; marin geologi; oseanografi

Shelf progradation on a glaciated continental margin, Queen Maud Land, Antarctica - Kristoffersen, Yngve; Winterhalter, Boris; Solheim, Anders (Marine Geology, 2000)
A detailed survey of the continental margin in the eastern Weddell Sea demonstrates shelf progradation by material input from discrete glacial wedges that amalgamate to form the present near rectilinear shelf edge. Kvitkuven Ice Rise is located between two trough mouth fans and rests on a thick sediment substratum that predates the shelf sequences north of it. Shelf progradation, west of the ice rise, preceded the progradation east of it. In this way the seaward progression of a shelf edge may reflect the broad scale expansion of the East Antarctic Ice Sheet, but the timing of shelf progradation can be different in adjacent areas. The progradational glacial wedges on the continental shelf mapped by this survey are correlated stratigraphically to be within the post Late Miocene glacial sequence, drilled at ODP Site 693 on the middle continental slope 200 km to the northeast. Two submarine moraine ridge complexes on the shelf parallel the shelf edge. A radiocarbon age of 18:950 280 years BP from the front of the inner complex (water depth 319 m) suggests that grounded ice at most reached the present mid-shelf area in front of the ice rise during the Late Wisconsin Glacial Maximum, or had retreated to this position at that time.
Keywords: Dronning Maud Land; Weddellhavet; marin geofysikk; marin geologi; oseanografi; seismisk stratigrafi

Antarktis i fokus - hva gjør norsk forskning? - Orheim, Olav (Forskningsnytt, 1975)
Keywords: Antarktis; NARE ekspedisjoner; geologi; glasiologi; havis; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; polarområdene